Implementasi Aplikasi Pemesanan Makanan dan Minuman Pada Kafe Kopi Andung Berbasis Web dengan Penerapan Metode RAD - Anisa Fitrianty; Taqrim Ibadi (Universitas Nahdlatul Ulama Blitar, 2025)
This study was conducted at Kopi Andung, a café located in Palembang, South Sumatra, where the ordering process was still carried out manually through the cashier, often causing service delays during peak hours. The research aimed to develop a web-based ordering system that facilitates more efficient service for customers while allowing café owners to monitor transactions virtually. The research was carried out from January to April 2025 using hardware and software instruments including Intel i7 processors, XAMPP, Sublime Text, and CodeIgniter. Data collection methods consisted of literature review, observation, and interviews, ensuring triangulation of data validity. The Rapid Application Development (RAD) method was applied, encompassing requirement planning, system design, development, and implementation stages. Results showed that the web-based system successfully accelerated the ordering process, reduced the risk of service delays, and improved customer satisfaction. The system was also proven to be adaptive to user feedback and operational needs. This research contributes to the field of information systems by demonstrating the practicality of the RAD model in developing café management solutions, providing both theoretical and practical implications for small businesses.